Metagenomic evidence for metabolism of trace atmospheric gases by high-elevation desert Actinobacteria - Lynch, Ryan C.; Darcy, John L.; Kane, Nolan C.; Nemergut, Diana R.; Schmidt, Steve K. (Frontiers in Microbiology, 2014)
Previous surveys of very dry Atacama Desert mineral soils have consistently revealed sparse communities of non-photosynthetic microbes. The functional nature of these microorganisms remains debatable given the harshness of the environment and low levels of biomass and diversity. The aim of this study was to gain an understanding of the phylogenetic community structure and metabolic potential of a low-diversity mineral soil metagenome that was collected from a high-elevation Atacama Desert volcano debris field. We pooled DNA extractions from over 15 grams of volcanic material, and using whole genome shotgun sequencing, observed only 75 - 78 total 16S rRNA gene OTUs3%. The phylogenetic structure of this community is significantly under dispersed, with actinobacterial lineages making up 97.9% - 98.6% of the 16S rRNA genes, suggesting a high degree of environmental selection. Due to this low diversity and uneven community composition, we assembled and analyzed the metabolic pathways of the most abundant genome, a Pseudonocardia sp. (56% - 72% of total 16S genes). Our assembly and binning efforts yielded almost 4.9 Mb of Pseudonocardia sp. contigs, which accounts for an estimated 99.3% of its non-repetitive genomic content. This genome contains a limited array of carbohydrate catabolic pathways, but encodes for CO2 fixation via the Calvin cycle. The genome also encodes complete pathways for the catabolism of various trace gases (H2, CO and several organic C1 compounds) and the assimilation of ammonia and nitrate. We compared genomic content among related Pseudonocardia spp. and estimated rates of non-synonymous and synonymous nucleic acid substitutions between protein coding homologs. Collectively, these comparative analyses suggest that the community structure and various functional genes have undergone strong selection in the nutrient poor desert mineral soils and high-elevation atmospheric conditions.